Pembuatan animasi 3d bertemakan islami dengan judul “cil & cil” dengan menerapkan metode pose to pose - Radianto, Aisha Dwi Anindita; Ridho, Muhammad; Hartanti, Aninda Rizky; Fantofani, Rizal; Karami, Ahmad Fahmi; Nugroho, Fresy (Maliki Interdisciplinary Journal, 2024)
The existence of feelings is a given for everyone with a soul. Owned emotions are neither exclusively good nor exclusively negative. Jealousy and envy are two of the many latent virtues in ugliness that must occasionally triumph against them. When we are resentful and jealous of another individual, we unwittingly hide their positive traits. Indeed, that individual must possess deficiencies that, when they are transformed into strengths by us, become a strength. As a result, we all require and enhance one another. This 3D animated movie was created with the intention of educating children and/or adults about the negative traits of envy and jealousy, which should be avoided since Allah does not like them. In order to catch the audience’s attention and help them benefit from the animated film, visualization in the form of 3D animation is planned to be used. Blender 3.3 software was used to create this 3D animation video.